Arthroscopic Excision of Osteoid Osteoma of the Talus - Iftach Hetsroni, M.D.; Meir Nyska, M.D.; Evgeny Edelshtein, M.D., Ph.D.; Gideon Mann, M.D.; Ezequiel Palmanovich, M.D. (Arthroscopy Techniques, 2017)
Osteoid osteoma is a benign tumor that can cause significant pain and disability. Excision of the tumor can be accomplished with open surgery or, as advocated in recent years, with computed tomography (CT)-guided radiofrequency ablation. In this article, a unique arthroscopic approach to excise an osteoid osteoma of the talus is presented. This was possible by relying on a clear intra-articular prominent osteophyte, which was used as a landmark to indicate tumor location in accordance with preoperative CT views. This technique enabled excision of the tumor with concomitant arthroscopic decompression of the osteophyte, which contributed to symptoms of anterior ankle impingement.